2012
DOI: 10.1097/gme.0b013e31826d2d94
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors, and predictors of pelvic organ prolapse

Abstract: Our findings suggest that cost-efficient interventions to reduce the burden of POP in this and similar remote communities include the following: family planning awareness campaigns focusing on the risks of grand multiparity; nutritional education and weight management programs to help reduce the progression of POP before the age of menopause; and consideration of symptom-based screening to identify affected women who might benefit from a referral to specialty care at a tertiary care center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
2
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 19 publications
3
46
2
7
Order By: Relevance
“…27 There is also a strong association between obesity and endometrial cancer, 47 and an association between obesity and pelvic organ prolapse. 48 …”
Section: Discussionmentioning
confidence: 99%
“…27 There is also a strong association between obesity and endometrial cancer, 47 and an association between obesity and pelvic organ prolapse. 48 …”
Section: Discussionmentioning
confidence: 99%
“…In the study by Awwad et al, 9 it was observed that POP prevalence was 20.4% for women aged 20 to 29 years, 50.3% for women aged 30 to 39 years, 77.2% for women aged 40 to 49 years, and 74.6% for women aged 50 to 59 years. The incidence of POP roughly doubled with each decade in women aged 20 to 59 years in the pelvic organ support study (POSST).…”
Section: Discussionmentioning
confidence: 90%
“…POP is the descent of pelvic organs into the vaginal canal and occurs with advanced age and vaginal parity [11][12][13]. It is associated with pelvic floor dysfunction and constitutes a major health problem, especially for women above 50 years old [14].…”
Section: Commentmentioning
confidence: 99%